Caroço de algodão na dieta de cabras leiteiras: parâmetros nutricionais e produtivos - Tassia Ludmila Teles Martins (2018)
The objective of this research is to examine the effects of feeding whole cottonseed on intake, performance and fatty acids profile. Eight lactating goats were used in two simultaneous 4x4 Latin square design, with four treatments and four periods of 21 days each. Treatments included whole cottonseed at increasing levels of 0, 120, 150 and 180% DM basis in a Total Mixed Ration. To estimate digestibility titanium dioxide was used as a digestibility marker. Milk yield and composition were evaluated. Blood samples were collected to analyze glucose, urea, non-esterified fatty acids, triglycerides, total cholesterol, total protein and albumin. Ingestive behavior was made during a 24 h period observing feeding, rumination and idle behaviors. Fatty acids profile was determined as some quality indexes of milk. Dry matter, crude protein and neutral detergent fiber intakes were not affected by inclusion of whole cottonseed, however a quadratic effect was observed in ether extract intake. Similar results were found for nutrient digestibility. Cholesterol concentrations presented a linear increase. Yield of milk and components was similar among treatments, but milk fat percentage increased with increasing levels of whole cottonseed in diet. Rumination time and efficiency were influenced by whole cottonseed on diet. Supplementation with whole cottonseed did not alter DMI, milk yield and composition and blood parameters. Short and medium chain fatty acids concentrations linearly decreased. Trans 18:1 fatty acids exhibited linear increase, while cis 18:1 fatty acids were not affected by treatments. Some polyunsaturated fatty acids showed a linear increase. Total CLA was not affected by inclusions of whole cottonseed. A linear increase was observed for mono and polyunsaturated fatty acids. Results from that experiment indicate that whole cottonseed improved goat milk fat nutritional value.